MAKNA DASAR PENDIDIKAN ISLAM (Kajian Semantik) - Karyanto, Umum B. (Forum Tarbiyah, 2011)
The concept or theory of education has a heated debatefor experts or scientists. In a semantic study of the meaning, in whichit is not composed only of a meaning or which it could be the opposite.In this case, the importance of education’s role is considered ingenerating a generation and it is not enough without accompanied bythe correct concept. If we accept as an empirical scientific theory asa paradigm in educational theory, it is realized or does not mean thatwe have abandoned the things that are metaphysical in the Qur’anand Sunnah. Scientific method in constructing a theory must be observedby the five senses. A theory that has not been proven empiricallycan not be relied upon in formulating a theory, including thetheory of education. In fact, the Qur’an which was revealed throughthe Prophet Muhammad, from time to time always develops its scientificmiracles’ proof, ranging from the past to the future, adjustingto the human ability in reading those miracle.